Особенности деформации металлов в сильных магнитных полях - Автономова, Людмила Владимировна; Степук, Александр Владимирович (НТУ "ХПИ", 2005)
Deformation mechanisms in pulse high magnetic fields are considered in the researching. The basic conclusions are as follows: non-uniformity of metals' deformation resulted on thermal effects of skin heating; raising of plasticity limit from surface to the sample depth up to its dynamic value; zero magnetic field pressure on surface does not prevent the metal structural modifications
Keywords: предел текучести; кристаллические решетки; пластическая деформация; фактор Шмидта